A method to assess the lifetime prolongation capabilities of products. (3rd July 2008) - Willems, B.; Dewulf, W.; Duflou, J.R.
To achieve a sustainable growth, it is necessary to pursue the decoupling of economic welfare from the use of virgin resources: a shift from a linear economy to a closed-loop economy is required. Consequently, adaptation processes such as maintenance, repair, upgrading and remanufacturing are needed. This paper presents a dedicated method to assess the lifetime prolongation capabilities of products by evaluating their design. The method determines the suitability of a product to undergo adaptation processes and the improvement potential within the design of a product, its components and joints, using an aggregated metric.